2009
DOI: 10.2337/dc08-0605
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients With Type 2 Diabetes in Primary Care in Norway Is Improving

Abstract: OBJECTIVE -To assess changes in the quality of care in Norway for patients with type 2 diabetes. RESULTS -Between 1995 and 2005, there were significant improvements in the proportion of patients for whom important laboratory analyses, smoking habits, height, weight, and referral to eye examination were recorded. Mean A1C declined from 7.74 to 7.15%, systolic blood pressure from 150.0 to 140.4 mmHg, and cholesterol from 6.28 to 5.0 mmol/l (P Ͻ 0.001, age and sex adjusted). The 10-year risk of coronary heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
(2 reference statements)
3
26
0
5
Order By: Relevance
“…570 (90.8%) of our patients had their BP documented, this rate is comparable to other studies, where more than 85% of patients attending the diabetic clinic had their blood pressure checked regularly [22,23,30,39].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…570 (90.8%) of our patients had their BP documented, this rate is comparable to other studies, where more than 85% of patients attending the diabetic clinic had their blood pressure checked regularly [22,23,30,39].…”
Section: Discussionsupporting
confidence: 74%
“…Despite the broadly distributed diabetes care guidelines, which give clear recommendations to the glycemic, blood pressure and lipid targets in diabetic patients, several studies have indicated that achievement of these targets is suboptimal [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Det at vi fant få studier er i seg selv interessant og understreker at vi mangler data for å konkludere sikkert om hvorvidt bruk av strukturerte skjemaer er et kostnadseffektivt tiltak. Til denne kategorien hører også NOKLUS-skjemaet (6).…”
Section: Diskusjonunclassified
“…Dette er ment å vaere både et klinisk verktøy for allmennlegen og et innsamlingsverktøy for Norsk diabetesregister (6). Det foreligger flere systematiske oversikter om effekten av ulike tiltak i diabetesoppfølgingen, men ingen omhandler spesifikt bruken av skjemaer for registrering av kliniske data (7).…”
unclassified